A Critical Review of Determined: Life Without Free Will: Author: Robert M. Sapolsky, Penguin Press, 2023, 528 pages - Whittaker, Max (Journal of NeuroPhilosophy, 2024)
The current paper critically appraises Robert Sapolsky’s recent popular science book, Determined (2023). Sapolsky’s basic claim is that there is much less scope for free will than many intuitively imagine, though book’s subtitle makes clear that free will is viewed as a wholly untenable concept. If there is no scientific basis for free will, Sapolsky argues, there is no basis for individual culpability, and little basis for society be organised around this principle. Modern forms incarceration, laden with notions of personal culpability, are thus unjustified. An instrumental use of quarantine, stripped of notions of guilt and shame, would represent a more rational, scientific approach towards those who behave dangerously. In response, the current review argues that the existence of free will is largely irrelevant to the question of individual responsibility. It also questions whether it is self-evident that society should be based upon a modern scientific understanding of human behaviour, while further arguing that scientific knowledge emerges from a professional culture grounded in individual accountability. Some cautionary reflections are then offered which challenge Sapolsky’s belief that more humane and compassionate societies will emerge if we dispense with notions of free will and personal culpability. Lastly, it will be argued that attributions of guilt and shame may not be wholly corrosive forces, but may in fact be instrumental in the maintenance stable and humane forms of human organisation.